Effects of Taurine on Phosphorylated Tau Protein Level in the Hippocampus of Scopolamine-Treated Adult Male Rats - Zeinab Asadi; Mehrdad Jahanshahi; Gholamhassan Vaezi; Seyed Mehran Hosseini (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: Taurine has many biological functions such as antioxidant and anti-inflammatory activities and acts as a neurotransmitter. But its effects on the tau phosphorylated protein levels require further studies. The aim of this study was to evaluate the protective and therapeutic effects of taurine on the level of tau phosphorylated protein in the hippocampus of rats treated with scopolamine. Materials and methods: In this research, 72 male Wistar rats were randomly divided into three groups: control, protection, and treatment groups. Protective and therapeutic groups were treated with different doses of taurine (25, 50, 100 mg/kg/day) for 14 days before or after injection of scopolamine (3 mg/kg). After the end of treatment, the extract of homogenized hippocampus tissue was collected to measure the level of tau phosphorylated protein using ELISA technique. Results: Protective injection of different doses of taurine significantly reduced the level of tau phosphorylated protein in the hippocampus compared to that in the protective sham group (p<0.001). Therapeutic injection of taurine at 50 mg/kg significantly decreased the level of tau phosphorylated protein compared with that of the therapeutic sham group. Conclusion: Protective and therapeutic injection of taurine can reduce the tau phosphoryl protein levels in the hippocampus of rats before or after the injection of scopolamine.